From talent to professional football - Youthism in German football - Grossmann, B.; Lames, M. (International Journal of Sports Science and Coaching, 2015)
The aim of this study was to investigate the impact of the German youth academies conducted by the clubs of 1st and 2nd Bundesliga and the role of the U17 Bundesliga as a part of the German talent development programme in football. We examined all 821 U17 Bundesliga players born in 1993 and tracked their career development until season 2012/13. It was found that less than 10% were able to sign a contract for a professional team in Germany (1st, 2nd and 3rd league), while more than 45% quit playing football before advancing onto senior level. 29 out of 36 (80.6%) 1st Bundesliga players born in 1993 (season 20012/13) were trained in a professional youth academy, two players were educated in a 4th league club and five players were transferred from a foreign country. Youth academies and the U17 Bundesliga are crucial for the development of German talents, since a very good football education with weekly challenges in league is beneficial. However, one can be worried about the physical as well as mental and emotional stress those young players are exposed to, which might lead to an earlier end of their careers.